Influence of side groups on the performance of infrared absorbing aza-BODIPY organic solar cells - Kraner, Stefan; Widmer, Johannes; Benduhn, Johannes; Hieckmann, Ellen; Jaegeler-Hoheisel, Till; Ullbrich, Sascha; Schuetze, Daniel; Radke, K. Sebastian; Cuniberti, Gianaurelio; Ortmann, Frank; Lorenz-Rothe, Melanie; Meerheim, Rico; et al. (physica status solidi (a), 2015)
Authoren Organic solar cells are a promising technology for a large area conversion of sunlight into electricity. In particular for solar cells based on oligomers (small molecules), efficient donor materials absorbing wavelengths larger than 780 nm are still rare. Here, we investigate three aza-BODIPY dyes absorbing in the infrared. The addition of side groups leads to a red shift of the optical gap from 802 to 818 nm. In optimized devices using these donors in a bulk heterojunction with C60, we observe a higher charge carrier mobility and a higher power conversion efficiency for the molecules without a methyl or methoxy side group lowering the molecular reorganization energy. Surprisingly, the donor-acceptor blend with the lowest energy loss during the electron transfer to the C60 yields the highest short circuit current. With increasing size of the attached side chain, the devices exhibit a larger trap density, measured by impedance spectroscopy. Based on the investigation of different blend ratios, we conclude that these traps are mainly present in the donor phase.
CRIS-Team Scopus Importer:2023-03-20
Keywords: aza-BODIPY; electron transfer losses; Infrared absorbers; organic solar cells; side groups; traps